2017
DOI: 10.1186/s12872-017-0642-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension with or without diabetes on left ventricular remodeling in rural Chinese population: a cross-sectional study

Abstract: BackgroundThe aim of this study was to assess the impact of hypertension with or without diabetes on left ventricular (LV) remodeling in rural Chinese population.MethodsA total of 10,270 participants were classified into control group, hypertension without diabetes (HT) group, and hypertension with diabetes (HT + DM) group. We compared clinical characteristics and echocardiographic parameters, and used multivariable logistic regression analysis to assess the associations of interest.ResultsHT + DM group had hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
5
17
0
Order By: Relevance
“…In the HyperGEN study comprising only hypertensive subjects, diabetes was independently associated to increased LV mass [ 35 ]. A recent Chinese study suggested additive effects of diabetes and hypertension to LV remodeling [ 36 ]. Although blood pressure reduction appears to be an effective way of lowering the risk of cardiovascular disease in hypertensive patients with increased LV mass, [ 37 ] these treatments do not seem to be as effective in patients with diabetes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the HyperGEN study comprising only hypertensive subjects, diabetes was independently associated to increased LV mass [ 35 ]. A recent Chinese study suggested additive effects of diabetes and hypertension to LV remodeling [ 36 ]. Although blood pressure reduction appears to be an effective way of lowering the risk of cardiovascular disease in hypertensive patients with increased LV mass, [ 37 ] these treatments do not seem to be as effective in patients with diabetes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was defined as having a systolic blood pressure (SBP) ≥ 140 mmHg and/or having a diastolic blood pressure (DBP) ≥90 mmHg and/or being under antihypertensive treatment. Diabetes was defined as fasting serum glucose (FPG) ≥7 mmol/L (126 mg/dL) and (or) being on treatment for diabetes [ 12 ]. Hyperlipidemia was defined as serum total cholesterol (TC) ≥6.22 mmol/L (240 mg/dL), or serum triglyceride (TG) ≥2.26 mmol/L (200 mg/dL), or serum low-density lipoprotein cholesterol (LDL-C) ≥4.14 mmol/L (160 mg/dL) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study that focused on normotensive type 2 diabetics, we also observed that PWTd, IVSTd and LVID progressively increased from control group to microalbuminuric group, which resulted in the increased LVM, LVMI and RWT, thereby influencing the LV geometry remodeling. Diabetes has been implicated in the pathogenesis of cardiovascular abnormalities such as higher and lower LVM, more concentric left ventricular geometry remodeling and a lower myocardial function independent of age, sex, body size and arterial blood pressure [3,6,[21][22]. These cardiovascular abnormalities are known to predict higher rates of cardiovascular events in both asymptomatic and symptomatic subjects and also contribute in part to the high rates of coronary heart disease and heart failure observed among diabetic patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is associated with diverse cardiovascular conditions such as myocardial infarction and heart failure (HF), which are the leading causes of diabetesrelated morbidity and mortality [1,2]. Previous studies elsewhere [3][4][5] and in Nigeria [6] have demonstrated left ventricular geometry remodeling and dysfunction in diabetics, supporting the existence of diabetic cardiomyopathy (DMCMP). The Framingham Heart Study showed that the frequency of HF is twice as high in diabetic men and five times higher in diabetic women compared with age-matched controls, and that this increased incidence of HF persisted despite correction for age, hypertension, obesity, hypercholesterolaemia and coronary artery disease (CAD) [7].…”
Section: Introductionmentioning
confidence: 99%